Breast cancer treatment: A phased approach to implementation - Mutebi, Miriam; Anderson, Benjamin O.; Duggan, Catherine; Adebamowo, Clement; Agarwal, Gaurav; Ali, Zipporah; Bird, Peter; Bourque, Jean‐Marc; DeBoer, Rebecca; Gebrim, Luiz Henrique; Masetti, Riccardo; Masood, Shahla; et al. (Cancer, 2020)
Optimal treatment outcomes for breast cancer are dependent on a timely diagnosis followed by an organized, multidisciplinary approach to care. However, in many low‐ and middle‐income countries, effective care management pathways can be difficult to follow because of financial constraints, a lack of resources, an insufficiently trained workforce, and/or poor infrastructure. On the basis of prior work by the Breast Health Global Initiative, this article proposes a phased implementation strategy for developing sustainable approaches to enhancing patient care in limited‐resource settings by creating roadmaps that are individualized and adapted to the baseline environment. This strategy proposes that, after a situational analysis, implementation phases begin with bolstering palliative care capacity, especially in settings where a late‐stage diagnosis is common. This is followed by strengthening the patient pathway, with consideration given to a dynamic balance between centralization of services into centers of excellence to achieve better quality and decentralization of services to increase patient access. The use of resource checklists ensures that comprehensive therapy or palliative care can be delivered safely and effectively. Episodic or continuous monitoring with established process and quality metrics facilitates ongoing assessment, which should drive continual process improvements. A series of case studies provides a snapshot of country experiences with enhancing patient care, including the implementation of national cancer control plans in Kenya, palliative care in Romania, the introduction of a 1‐stop clinic for diagnosis in Brazil, the surgical management of breast cancer in India, and the establishment of a women's cancer center in Ghana. Optimal breast cancer patient outcomes are dependent on a timely diagnosis followed by an organized, multidisciplinary approach to treatment; however, in many low‐ and middle‐income countries, effective care management pathways can be difficult to follow. On the basis of previous work by the Breast Health Global Initiative, this consensus manuscript proposes a phased implementation strategy for sustainable systematic approaches to enhancing breast cancer treatment for patients in limited‐resource settings.